Dense, continuous membrane labeling and expansion microscopy visualization of ultrastructure in tissues - Tay Won Shin; Hao Wang; Chi Zhang; Bobae An; Yangning Lu; Elizabeth Zhang; Xiaotang Lu; Emmanouil D. Karagiannis; Jeong Seuk Kang; Amauche Emenari; Panagiotis Symvoulidis; Shoh Asano; et al. (Nature Communications)
Abstract Lipid membranes are key to the nanoscale compartmentalization of biological systems, but fluorescent visualization of them in intact tissues, with nanoscale precision, is challenging to do with high labeling density. Here, we report ultrastructural membrane expansion microscopy (umExM), which combines an innovative membrane label and optimized expansion microscopy protocol, to support dense labeling of membranes in tissues for nanoscale visualization. We validate the high signal-to-background ratio, and uniformity and continuity, of umExM membrane labeling in brain slices, which supports the imaging of membranes and proteins at a resolution of ~60 nm on a confocal microscope. We demonstrate the utility of umExM for the segmentation and tracing of neuronal processes, such as axons, in mouse brain tissue. Combining umExM with optical fluctuation imaging, or iterating the expansion process, yields ~35 nm resolution imaging, pointing towards the potential for electron microscopy resolution visualization of brain membranes on ordinary light microscopes.